The Impact of Civic Education in a Divided Society: the Case of Cameroon - Tanto, Ngie Didemus (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
The goal of this thesis is to make an analysis of the role of civic education policies initiated by Cameroon in overcoming the Francophone/Anglophone division. In this study, the research question is raised: Is civic education effective in overcoming the Francophone/Anglophone division in Cameroon? In an effort to provide an answer to this question and accomplish the goal of this study, the researcher made use of a qualitative research method. Data collection in this study was obtained through publications from Cameroon Ministry of Youth Affairs and Civic Education and non-governmental organizations, academic articles, textbooks, journals, documentaries and internet material. In examining the effectiveness of civic education in overcoming division, the researcher made use of the liberal civic education model. This model provides an explanation on how core civic liberal values such as the rule of law, equality, tolerance, mutual respect, good governance, freedom of expression, freedom of worship and respect of minority rights can overcome division in a society. The conclusion reached is that civic education should be given greater concern and resources. Furthermore, there is a need for political will to effectively implement core civic values by the Ministry of Youth Affairs and Civic Education.

ÖZ: Bu tezin ana amacı Kamerun‘da başlatılan eğitim politikalarının Fransızca/İngilizce konuşanlar arasındaki ayrımın üstesinden gelmekteki rolünü analiz etmektir. Bu çalışmanın ana araştırma sorusu şudur: Kamerun‘da kamusal eğitim Fransızca konuşanlar/İngilizce konuşanlar ayrımının aşılmasında etkili midir? Bu soruyu cevaplamak ve bu çalışmanın amacını gerçekleştirmek amacıyla ,araştırmacı nitel bir araştırma yöntemi kullanmıştır. Bu çalışmadaki veriler, Kamerun Gençlik İşleri ve Yurttaşlık Eğitimi Bakanlığı‘nın yayımladığı kaynaklar, sivil toplum örgütlerinin yayınları, akademik makaleler ,ders kitapları, gazeteler, belgeler ve internet yayınlarından elde edildi. Araştırmacı, toplumsal eğitimin bölünmenin üstesinden gelmedeki etkinliği incelerken, liberal yurttaşlık eğitim modelini kullanmıştır. Bu model, hukukun üstünlüğü, eşitlik, hoşgörü, karşılıklı saygı, iyi yönetişim, ifade özgürlüğü, iş özgürlüğü ve azınlık haklarına saygı gibi temel liberal yurttaşlık değerlerinin toplumdaki bölünmeyi nasıl aşabileceğini açıklamaya yardımcı olur. Bu araştırmadan elde edilen sonuç, yurttaşlık eğitimine daha fazla ilgi gösterilmesi ve kaynak ayrılmasının gerekli olduğudur. Bundan da ötesi, Gençlik İşleri ve Yurttaşlık Eğitimi Bakanlığı‘nın temel vatandaşlık değerlerini etkili bir şekilde uygulayabilmesi için siyasi iradeye ihtiyaç vardır.
Master of Arts in International Relations. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2018. Supervisor: Prof. Dr. Erol Kaymak.
Keywords: Political Science and International Relations; Civics--Study and teaching--Cameroon; Education Policy--Cameroon; Civics (Citizenship) Education--Cameroon; Civic Education; divided society; education; civic; society; Cameroon